Electricity Outages and Health Outcomes of Children: Empirical Evidence from Transition Economy - Yermone Sargsyan (Charles University in Prague, Institute of Economic Studies (IES), 2021)
The electricity prices in developing countries are relatively low to recover its costs of generation and provision. This results in under-investment in infrastructure, which usually leads to frequent outages or rolling blackouts by the electricity suppliers. Outages may have an adverse impact on the household's welfare including the health of household members. Using household-level panel data "Life in Kyrgyzstan" (LIK), and a coarsened exact matching (cem) procedure this paper investigates whether there is a relationship between outages and the health of children. Specifically, I study the differences in the anthropometric outcomes of children aged 5 and below (given by the z-scores) living in households that experience frequent outages and those which do not. I find that the children living in the households with frequent outages have z-scores of height-for-age that are -0.334 units lower, and z-scores of weight-for-age that are -0.157 units lower than compared to the children living in the observationally identical households but without frequent outages.
Keywords: I12; I14; J13; P36; Q53; Q41; 330; electricity outages; child health; height-forage; weight-for-age; developing countries; transition economies